1999
DOI: 10.1017/s0022112099006618
|View full text |Cite
|
Sign up to set email alerts
|

The current-modified nonlinear Schrödinger equation

Abstract: By comparison with both experimental and numerical data, Dysthe's (1979) O(ε4) modified nonlinear Schrödinger; equation has been shown to model the evolution of a slowly varying wavetrain well (here ε is the wave steepness). In this work, we extend the equation to include a prescribed, large-scale, O(ε2) surface current which varies about a mean value. As an introduction, a heuristic derivation of the O(ε3) current-modified equation, used by Bakhanov et al. (1996), is given, before a more formal approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 22 publications
1
50
0
Order By: Relevance
“…Trulsen & Dysthe 1996) that only allows for a limited time horizon, τ , for the calculations of the order of (ω p s 3 ) −1 , where ω p = 2π/T p . Quantitative comparisons with wave tank experiments and other numerical wave models (Lo & Mei 1985;Trulsen & Stansberg 2001;Shemer et al 2001Shemer et al , 2002Stocker & Peregrine 1999;Clamond & Grue 2002) have indicated that a reasonable time horizon is indeed τ ≈ (ω p s 3 ) −1 , which for the present simulations (with…”
Section: The Simulation Modelsupporting
confidence: 73%
“…Trulsen & Dysthe 1996) that only allows for a limited time horizon, τ , for the calculations of the order of (ω p s 3 ) −1 , where ω p = 2π/T p . Quantitative comparisons with wave tank experiments and other numerical wave models (Lo & Mei 1985;Trulsen & Stansberg 2001;Shemer et al 2001Shemer et al , 2002Stocker & Peregrine 1999;Clamond & Grue 2002) have indicated that a reasonable time horizon is indeed τ ≈ (ω p s 3 ) −1 , which for the present simulations (with…”
Section: The Simulation Modelsupporting
confidence: 73%
“…Note that a term of that kind arises in the Eulerian description of potential wave oscillations of the free surface as well. In the paper by Stocker and Peregrine (1999), U = U * sin (kx − ω t) was chosen and interpreted as a harmonically changing surface current induced by an internal wave. We shall further take U = 0.…”
Section: Cubic Approximationmentioning
confidence: 99%
“…Higher-order expansions in terms of nonlinearity and wave dispersion have been used to derive more general Schrödinger-like models for water waves including currents [22]. In the formalism of Ref.…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…In the formalism of Ref. [22], the current velocity is of order 2 , while the time and space derivatives and Ak 0 are of order , where is a nonlinearity parameter. Since the dispersion and nonlinearity coefficients D x and −ξ have equal signs, Eq.…”
Section: Mathematical Formulationmentioning
confidence: 99%